The Effect of Prenatal Yoga on Lowering Blood Presure in Pregnant Women at Lubuk Baja Public Health Center - Catur Yulinawati; Mona Rahayu Putri; Hazen Aziz (Universitas Muhammadiyah Manado, 2024)
Increased blood pressure is very influential, especially if it occurs in pregnant women. If it is not treated properly, it can make the situation worse, causing complications called preeclampsia. As many as 62,000-77,000 deaths every year and 18.1% are caused by preeclampsia. Prenatal yoga exercises are a non-pharmacological therapy that can lower blood pressure by relaxing muscles and relaxing breathing which can stabilize emotions, eliminate anxiety, calm the mind and increase concentration and body balance. This study aims to determine whether there is an effect of prenatal yoga exercises on reducing blood pressure in pregnant women at the Lubuk Baja Community Health Center. The method in this research is a Quasy Experimental type of research using a One Group Pretest-Posttest Design. The sampling technique used was Total Sampling, and data collection techniques were through interviews and secondary data. There were 15 pregnant women who experienced an increase in blood pressure. Results: The statistical test used was Paired Sample T-Test with P-Value 0.000 < 0.05. Conclusion: This research shows the effect of prenatal yoga exercises on reducing blood pressure in pregnant women. Suggestion: It is hoped that all health workers and health services can make promotive and preventive efforts in an effort to reduce blood pressure, especially in pregnant women.